Edukasi Dan Pemahaman Perpajakan Sebagai Upaya Peningkatan Kepatuhan Pelaporan SPT Era Coretax - Febby Balla Syach Puteri; Iftita Dewi Karisma; Amrizal Imawan (JURNAL AKUNTANSI AUDIT DAN PERPAJAKAN INDONESIA (JAAPI), 2026)
This study aims to analyze the role of tax education and tax understanding in improving taxpayer compliance in filing Annual Tax Returns (SPT) during the implementation of the Coretax Administration System. The study employed a qualitative descriptive approach conducted at KPP Pratama Lamongan. Data were collected through in-depth interviews, observation, and documentation involving one tax officer and four individual taxpayers selected using purposive sampling. The findings indicate that tax education delivered through socialization programs, official social media, the Directorate General of Taxes website, webinars, and consultation services has helped taxpayers understand tax regulations and adapt to the Coretax system. The study also found that better tax understanding supports taxpayers in fulfilling their tax obligations accurately and on time. However, the implementation of Coretax still presents challenges due to taxpayers' limited familiarity with the new digital system. Overall, tax education and tax understanding play an important role in improving taxpayer compliance in Annual Tax Return reporting during the Coretax era. Therefore, continuous education, assistance, and simplification of Coretax-related information are needed to support successful digital tax administration